PENGARUH KUALITAS MAKANAN, CITRA MEREK, LOKASI USAHA DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADATOKO ROTI HASANAH BAKERY RANTAUPRAPAT - Br Sitepu, Dona Laurika; Safri, Hayanuddin; Marto Hendry, Raja Saul (Universitas Labuhanbatu, 2021)
This study aims to determine and analyze the influence of food quality, brand image, location and price on purchase decisions in the Store Bread Hasanah Bakery Rantauparapat. The population in this research is the customers at the Bakery Hasanah Bakery Rantauprapat, where the determination of the sample is by using the technique of random sampling by using the formula Wibisono. Data collection techniques using a questionnaire as the research instrument of the first test the validity and reliability of the instrument. Analysis of the data by using a hypothesis test, where the data of the first test, the classical assumption in the form of normality test, multicollinearity test and heterokedastisitas. The results showed that the Quality of the food (X1) has positive and significant effect on purchasing decisions (Y) on the Bakery Hasanan Bakery with a value of t1hitung of 2,439 > ttable of 1,660 with significance to 0.011 < 0.005. Brand image (X2) and the positive effect on the purchase decision (Y) on the Bakery Hasanan Bakery with a value of t2hitung of 2,340 > ttable of 1,660 with significance 0,021 < 0.005.The location of the business (X3) have a positive and significant impact on purchasing decisions (Y) on the Bakery Hasanan Bakery with a value of t3hitung of 3,140 > ttable of 1,660 with significance to 0.002 < 0.005.Price (X4) have a positive and significant impact on purchasing decisions (Y) on the Bakery Hasanan Bakery with a value of t4hitung by 4.824 > ttable of 1,660 with significance 0.000 < 0.005.Simultaneous food quality, brand image, the location of the business and the price has positive and significant effect on purchase decisions in the Store Bread Hasanan Bakery with a value of Fcount 123,875 < from Ftable 3.09 with a significance level of 0.000 > 0.05 at confidence level 95% and Alpha of 5%.